INTERNALISASI NILAI-NILAI MULTIKULTURAL DALAM PROSES PEMBELAJARAN PAI DI SMA DARUT TAQWA, PASURUAN - Makhfud Syawaludin (Universitas Yudharta Pasuruan, 2019)
This research explains the internalization of multicultural values ​​in the learning process of PAI at Senior high school Darut Taqwa Sengonagung Purwosari Pasuruan. This Research uses a qualitative approach with the type of case study. The data collection was through by unstructured and opened interview techniques, unattended and opened observation, and documentation techniques. For analysis and interpretation of data using steps: a). Reduction data, b). Displaying data, and c). Conclusion drawing / verification. The results of the research shows that the internalization of multicultural values ​​in the learning process of PAI through two ways, namely through the material and using methods that reflect multicultural values.